LINGUISTIC VARIATION IN ECONOMIC RESEARCH ARTICLE ABSTRACTS BETWEEN ENGLISH AND INDONESIAN: A SYSTEMIC-FUNCTIONAL ACCOUNT - Donald Jupply; Susana Widyastuti (LITERA, 2022)
Considerable work on contrastive text analysis of abstracts has been conducted between English and other languages to explore the uniqueness between them. However, as far as methodology and language pair are concerned, there remains a paucity of research between English and Indonesian abstracts, and, in particular, in the usage of Systemic Functional Linguistics (SFL) for the purposes of translation. Using annotated and manually collated comparable corpora of abstracts collected from English and Indonesian academic articles (Bulletin of Indonesian Economic Studies-ANU and DINAMIKA-UNES), this study aims to contrast textual profiles of English and Indonesian abstracts in the field of economics. Based on the results of the analysis on the three metafunction in language at the stratum of lexico- grammar, this study suggests that marked differences between the comparable corpora of English and Indonesian abstracts are in the experiential and textual meanings. The implication of this study is that abstract translators from Indonesian into English need to pay a closer attention to the two metafunction in order to attempt an acceptable English translation.